Response to Adrian Ryan - Ralphs, John D. (Journal of Scientific Exploration, 2013)
Thank you very much indeed for your helpful correction to my JSE article "Magnetic Anomalies and the Paranormal" (Ralphs 2012). I am not surprised at the error, as my last serious consideration of cosmic rays was seventy years ago (I qualified in 1943). But I hope that you agree that it does not affect the point I hoped to make, that the simulation of magnetic anomaly effects using magnetic fields only cannot claim to be complete or authoritative.